Ecological validity and inclusivity in heritage bilingualism research: Examining objective and subjective Spanish proficiency assessments and language experience factors - Luque, Alicia; Koronkiewicz, Bryan; Issa, Bernard; Faretta-Stutenberg, Mandy; Bowden, Harriet Wood (Frontiers in Language Sciences, 2025)
The multidimensional nature of bilingualism demands ecologically valid and inclusive research methods that can capture its dynamism and diversity. This is particularly relevant when assessing language proficiency in minoritized and racialized communities, including heritage speakers (HSs). Motivated by a paradigm shift in bilingualism research, the present study joined current efforts to establish best practices for assessing language proficiency among bilingual individuals accurately and consistently, promoting ecological validity and inclusivity. Specifically, we examined the reliability and validity of objective and subjective proficiency assessments ubiquitously used in second language (L2) and bilingualism research to assess Spanish proficiency, within a sample of HSs of Spanish in the United States (US). We also sought to understand the relationships between these proficiency assessments and a subset of heritage language (HL) experience factors. To our knowledge, this is the first study to examine the reliability and validity of these proficiency assessments and their relationship with HL experience factors with HSs of Spanish in the US in a multidimensional way. Forty-three HSs of Spanish completed the Bilingual Language Profile questionnaire (Birdsong et al., 2012), including self-reports of proficiency and information about HL experience and two objective proficiency assessments: a lexical decision task, namely the LexTale-Esp (Izura et al., 2014), and a vocabulary and grammar task, often referred to as the "Modified DELE" (Montrul, 2012). Our findings revealed high internal consistency for both objective proficiency assessments and medium correlations between them, supporting their reliability and similarity. However, our results also revealed inconsistent relationships between subjective proficiency assessments and HL language experience factors. These findings underscore the dynamic interplay between these HSs' objective and subjective proficiency, and HL experiences and use across different contexts. Additionally, they highlight the limitations of relying on any single proficiency assessment, aligning with previous research that emphasizes the need for multidimensional proficiency assessments and language experience factors to capture the dynamic and diverse nature of bilingualism.